The Mediating Role of Critical Thinking Abilities in the Relationship Between English as a Foreign Language Learners’ Writing Performance and Their Language Learning Strategies - Esmaeil Nejad, Maryam; Izadpanah, Siros; Namaziandost, Ehsan; Rahbar, Behzad (Frontiers in psychology, 2022)
Recent developments in the field of education have led to a renewed interest in the mediating role of critical thinking abilities (CTA) in the relationship between language learning strategies and the intermediate English as a Foreign Language (EFL) learners’ writing performance. Oxford Placement Test (OPT) was run to homogenize the participants, and 100 intermediate learners out of 235 were selected. Then, two valid questionnaires of Ricketts’ Critical Thinking Disposition and Oxford’s Strategy Inventory for Language Learning were administered. Having administered the questionnaires, the researchers asked the participants to sit for a writing test. The data collected from the questionnaires and as well as the scores of their writing performances were analyzed through SPSS (25.00). The results showed a significant relationship between (a) learning strategies and learners’ writing performances, (b) the sub-sets of learning strategies and learners’ writing performances, and (c) CTA and learners’ learning strategies. However, CTA did not play a mediating role in the relationship between intermediate EFL learners’ learning strategies and writing performance. Based on the results of the study, one might also conclude that strategies seemed to play a more important role in the performance of learners especially their writing performances. Therefore, this study had useful contributions for students, teachers, and curriculum designers. Findings of this research could assist teachers to be aware of learners’ strategies in learning writing and help their students to be responsive to using learning strategies in their learning process and create a satisfactory learning context for using learning strategies. Therefore, learners were able to become independent and feel responsibility for their own learning. Secondly, curriculum developers could take advantage of the findings to include learning strategies training into the curriculum. As a result, students were able to use strategies in their learning process more easily and finally, the results might pave the way for improving the research findings.